2020
DOI: 10.1177/0734242x20941099
|View full text |Cite
|
Sign up to set email alerts
|

A fair CoP? MRF sampling, testing and reporting: Big problems caused by small particles. Part 1: Compliance difficulties and data validity

Abstract: The Regulations governing Materials Recovery Facilities (MRFs) in England require that they report on the quality of both the incoming mixed wastes and the single-stream recyclate products, with the results being made available on a public register. In this investigation, tests were conducted on a number of mixed wastes from different suppliers being processed at a qualifying MRF to evaluate how effective the Regulations (or MRF Code of Practice (MRF CoP)) were in generating useful, meaningful information. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Kirk and Mokaddam (In press) have indicated that the separation of the statutorily-defined material particles from the bulk materials in the MWs cannot be achieved by the recommended methodology. Accordingly, any materials that would be separated using the currently recommended screening process are named ‘quasi-material particles’ (q-MPs) throughout this article to distinguish them from the statutorily-defined ‘material particles’ of the MRF CoP.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kirk and Mokaddam (In press) have indicated that the separation of the statutorily-defined material particles from the bulk materials in the MWs cannot be achieved by the recommended methodology. Accordingly, any materials that would be separated using the currently recommended screening process are named ‘quasi-material particles’ (q-MPs) throughout this article to distinguish them from the statutorily-defined ‘material particles’ of the MRF CoP.…”
Section: Methodsmentioning
confidence: 99%
“…As was the case for the first part of this investigation (Kirk and Mokaddam, 2021), thanks are due to all who assisted -in particular Ashlie Haste, Quality Control Manager at Bywaters (Leyton) Limited and her staff who carried out most of the sampling and hand-sorting of the mixed wastes to generate the hard data. Thanks, too, to those who continued to have their ears bent and brains picked during the writing period -Charnell Dry, Mick Fegan and Dave Watt being foremost here.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 14 articles selected, one was at country level, six investigated MRFs as part of the MSW management system of a city or region, six were on plant level only, and one was at the level of a paper factory that received waste paper from different MRFs. Four studies were related to the UK (Kirk & Mokaddam, 2021a, 2021bMiranda et al, 2013;Wang et al, 2020) and Spain (Ip et al, 2018;Istrate, Medina-Martos, et al, 2021;Miranda et al, 2013), and three to Italy (Ardolino et al, 2017;Gadaleta et al, 2020;Mastellone et al, 2017). One study each was on Portugal, Germany, Austria and without any reference (Cimpan et al, 2016;Dias et al, 2014;Griffiths et al, 2010;Warrings & Fellner, 2021).…”
Section: Materials Recovery Facilitiesmentioning
confidence: 99%